2015
DOI: 10.1073/pnas.1507587112
|View full text |Cite
|
Sign up to set email alerts
|

Vascular disease-causing mutation R258C in ACTA2 disrupts actin dynamics and interaction with myosin

Abstract: Point mutations in vascular smooth muscle α-actin (SM α-actin), encoded by the gene ACTA2, are the most prevalent cause of familial thoracic aortic aneurysms and dissections (TAAD). Here, we provide the first molecular characterization, to our knowledge, of the effect of the R258C mutation in SM α-actin, expressed with the baculovirus system. Smooth muscles are unique in that force generation requires both interaction of stable actin filaments with myosin and polymerization of actin in the subcortical region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
96
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 53 publications
6
96
2
Order By: Relevance
“…The R258 residue, which corresponds to amino acid R256 in the actin protein due to posttranslational processing that removes the N-terminal Met and Cys residues (18), lies at the interface between the two strands of filamentous actin. Mutation of R258 to C or H is understood to disrupt allosteric communication to binding sites on the surface of actin (17,19). Intermediate effects on SM α-actin functions were observed in 1:1 mixtures of WT and R258C proteins, consistent with anticipated disruption of actin-dependent properties in heterozygous smooth muscle cells of patients harboring this mutation.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The R258 residue, which corresponds to amino acid R256 in the actin protein due to posttranslational processing that removes the N-terminal Met and Cys residues (18), lies at the interface between the two strands of filamentous actin. Mutation of R258 to C or H is understood to disrupt allosteric communication to binding sites on the surface of actin (17,19). Intermediate effects on SM α-actin functions were observed in 1:1 mixtures of WT and R258C proteins, consistent with anticipated disruption of actin-dependent properties in heterozygous smooth muscle cells of patients harboring this mutation.…”
mentioning
confidence: 71%
“…Effects of the mutation on fibroblast motility and contraction are remarkably consistent with predictions from biophysical studies on expressed vascular actins, but not unsurprisingly so. In vitro studies with expressed actins showed that the R258C mutation leads to defects in multiple facets of SM α-actin properties, including reduced actin filament stability and less productive interactions with smooth muscle myosin (17). However, in 50:50 mixtures of WT and R258C, polymerization rates were intermediate and skewed more toward the rate observed for WT SM α-actin.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in α-smooth muscle isoactin (αSMA) cause vascular defects leading primarily to thoracic aneurysm and dissection (TAAD). In PNAS, Lu et al (3) addresses two of these mutations, primarily R258C and secondarily R258H, to try to gain insight into how changes induced by these mutations lead to TAAD by affecting actin function. Vascular material from an affected individual carrying the R258C mutation shows that the muscle layer of the vessel wall is abnormal, with disorganized structure and a dearth of contractile filaments compared with normal smooth muscle, suggesting abnormal filament assembly, protein instability, or failure of the assembled cytoskeleton to withstand the forces imposed on it by myosin during contraction of the muscle (4,5).…”
mentioning
confidence: 99%
“…Lu et al (3) show that the R258C mutation in smooth muscle actin resulted in a decreased rate of polymerization compared with that of WT actin, a less stable filament, and increased susceptibility to severing by the filament-severing protein cofilin (10). Earlier yeast work showed that polymerization rates and filament stability were similarly affected by the corresponding R258H mutation.…”
mentioning
confidence: 99%
See 1 more Smart Citation